Occurrence of triatomines (Hemiptera, Reduviidae) and their natural infection by Trypanosoma cruzi (Chagas, 1909) in Boca do Moa community, Cruzeiro do Sul, Acre, Brazil - Jesus, Adila Costa de; Madeira, Fernanda Portela; Silva Moraes, Madson Huilber da; Morais, Adson Araujo de; Oliveira, Jader de [UNESP]; Rosa, Joao Aristeu da [UNESP]; Aranha Camargo, Luis Marcelo; Oliveira Meneguetti, Dionatas Ulises de; Berrnarde, Paulo Sergio (Soc Brasileira Medicina Tropical, 2021)
Introduction: Triatomines are insect vectors of Trypanosoma cruzi, the etiological agent of Chagas disease. Methods: Triatomines were collected from households and by dissecting palm trees in the peri-urban areas of Cruzeiro do Sul (Acre); they were identified using a specific key and via genital analyses. Trypanosomatid infection was determined through microscopy and polymerase chain reaction. Results: In total, 116 triatomines of the species Eratyrus mucronatus, Rhodnius pictipes, R. stali, and R. montenegrensis were collected, of which 13.8% were positive for T. cruzi. Conclusions: Four species of triatomines presented an infection rate above 13% in the Boca do Moa community.
Keywords: Chagas disease; Trypanosomatids; Western Amazon